Exploring the impact of a parent-designed family literacy programme in a DEIS primary school on family literacy practices, home school-relationships and confidence - Kennedy, Maria (Trinity College Dublin. School of Education. Discipline of Education, 2024)
This doctoral research is set in an urban DEIS (Delivering Equality of Opportunity in Schools) band 1 primary school (a school at risk of educational disadvantage) in Ireland and explores family literacy, home-school relationships and educational disadvantage. This action research was conducted considering Bronfenbrenner's bioecological theory and offers a mechanism to interrogate the complex interactions involved in family literacy programmes by considering the 'process', 'person', 'context' and 'time'. By collaborating with a group of parents of children in first class in the school (known as the Parent Expert Group (PEG)) to design a set of tailored family literacy workshops for parents and children in Early Start and junior infants, this research provides an understanding of how this type of support may influence a) family literacy, b) home-school links and relationships and c) parental confidence and capacity to support their child's language and literacy development. Opportunities for democratic dialogue were prioritised, and a methodology that valued the participant's voices and experiences was implemented. This research endeavoured to take a non-deficit stance, welcoming all input from participants as shared constructors of this set of family literacy workshops. Twenty-eight families attended the PEG-designed workshops. Workshop participants engaged in semi-structured interviews, pre and post-workshop. The key findings show that the strong pre-existing home-school relationships in this disadvantaged school were fostered, family literacy practices were developed, the language and literacy development of the children and their families was supported, and parental confidence increased. This research facilitated opportunities to increase parent's capacity to recognise themselves as their child's primary educator, a key aim of the Home School Community Liaison scheme in Ireland. Furthermore, it has highlighted parents as partners in their child's education and operationalised this in a viable and valuable way. This research was a success, as outlined by parents and has implications for policy, practice and future research. The findings oppose the literature that takes a deficit stance on family literacy and parental engagement in areas of low socio-economic status and instead highlights the motivations and interests of these parents in supporting their child's language and literacy development.
APPROVED
Keywords: parental engagement; home-school relationships; partnerships in education; educational disadvantage; action research; family literacy; Home School Community Liaison